(untitled) - Rosenberg, Donna (Illinois, 1998)
World Mythology is a compilation of over 50 great myths and epics. Your students will gain an appreciation and understanding of ancient and modern cultures through myths and epics from the Middle East, Greece and Rome, the Far East and Pacific islands, the British Isles, Northern Europe, Africa, and the Americas. An introduction and historical background supplement each myth. Questions at the end of each selection prompt analysis and response..
Keywords: Mythology